Diagnosis and Management of Adrenocortical Carcinoma with co-secretion of Cortisol and Aldosterone - Meghan Marie Aliño; Lyzanne Maryl Tam-Go (Journal of the ASEAN Federation of Endocrine Societies)
Adrenocortical carcinoma (ACC) accounts for 0.05-2% of all malignant tumors. Forty-five percent of ACCs with secretory function have excess glucocorticoids alone and only less than 1% secrete aldosterone.